1989
DOI: 10.1001/jama.1989.03430100086034
|View full text |Cite
|
Sign up to set email alerts
|

Health and Mental Health Problems of Homeless Men and Women in Baltimore

Abstract: A study of homeless people in Baltimore, Md, focused on their health and other characteristics, with special emphasis on their needs for services. In the first stage, 298 men and 230 women were randomly selected from the missions, shelters, and jail in Baltimore to respond to a baseline interview that provided extensive sociodemographic and health-related data. In the second stage, a subsample of 203 subjects was randomly selected from the baseline survey respondents to have systematic psychiatric and physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
172
3
3

Year Published

1990
1990
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(193 citation statements)
references
References 15 publications
15
172
3
3
Order By: Relevance
“…Diabetes, hypertension, hyperlipidemia, and sleep apnea are a few examples of complications that are exaggerated by obesity in people with schizophrenia. 9 In addition, the overall mortality rate in this population has been reported to be almost double that of the general population. 10 Weight gain associated with antipsychotics may also be detrimental to treatment compliance and needs to be addressed with individual pa- 11 Given the potential for such adverse effects of weight gain and the superior efficacy of atypical antipsychotics in the treatment of patients with schizophrenia and schizoaffective disorders, the control of obesity in this group of patients is clinically important.…”
Section: Discussionmentioning
confidence: 86%
“…Diabetes, hypertension, hyperlipidemia, and sleep apnea are a few examples of complications that are exaggerated by obesity in people with schizophrenia. 9 In addition, the overall mortality rate in this population has been reported to be almost double that of the general population. 10 Weight gain associated with antipsychotics may also be detrimental to treatment compliance and needs to be addressed with individual pa- 11 Given the potential for such adverse effects of weight gain and the superior efficacy of atypical antipsychotics in the treatment of patients with schizophrenia and schizoaffective disorders, the control of obesity in this group of patients is clinically important.…”
Section: Discussionmentioning
confidence: 86%
“…Reports of the prevalence of depressive disorders (e.g., major affective disorder, major depressive episode, major unipolar depression) among homeless women range from 18% to 37% (Breakey et al, 1989;Koegel et al, 1988;North et al, 1997;Smith et al, 1993). In addition, Nyamathi et al (1997) found that 84% of homeless and drug-addicted women reported emotional disturbance (e.g., depression, lack of emotional well-being).…”
Section: Psychosocial Problems Related To Homelessnessmentioning
confidence: 99%
“…In addition, Nyamathi et al (1997) found that 84% of homeless and drug-addicted women reported emotional disturbance (e.g., depression, lack of emotional well-being). Despite the consistency in the high prevalence rates of depression, few empirical investigations have focused on the comorbidity of substance abuse and depression among homeless women (e.g., Breakey et al, 1989;Nyamathi et al, 1997;Smith et al, 1993).…”
Section: Psychosocial Problems Related To Homelessnessmentioning
confidence: 99%
“…Homeless persons are among the most vulnerable groups in society and suffer from high rates of physical illness, mental health disorders, and substance abuse (2,3). Several cohort studies conducted over the past decade indicate that increased morbidity among the homeless predictably leads to worse survival and excess healthcare costs (4,5).…”
Section: Introductionmentioning
confidence: 99%